Propuesta para la mejora del clima organizacional en microempresas en Colombia (2018)
The commercial premises and / or micro companies, nowadays, do not have established as such a system of incentives or compensations for their workers in comparison with the big companies, where they have established even in what proportion the profitability was increased or what qualitative benefits they were obtained from it. The organizational climate of an entity is as important as an optimization of resources to obtain higher profits, hence its preponderant role.